Parenting : - Hildebrand, Verna (Glencoe/McGraw-Hill, 1997)
This thoroughly updated edition of Parenting: Rewards & Responsibilities is designed to help teens develop the skills and gain the knowledge that will help them become better parents—now or in the future. Students will learn why they need to take the responsibilities of parenting seriously, how good management and interpersonal skills are relevant to parenting, guidelines for physical care, health and safety of children, and how to nurture children's intellectual, emotional, social and moral development.